The Influence of Talent Management on Employee Performance with Organizational Commitment as a Mediating Variable - Rahman, Abdul; Sriwiyani, Sriwiyani; Ahmed, Abdal (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to provide empirical evidence and develop a theory-oriented prediction regarding the influence of talent management on employee performance, mediated by organizational commitment in madrasas. The study employed an explanatory approach with a survey method. Data were collected from 30 respondents, who served as the research sample, using a random sampling technique. Data analysis was conducted using the Partial Least Squares (PLS) method in SmartPLS. The results indicate that talent management positively affects performance and organizational commitment. The better the implementation of talent management, through the identification, development, and retention of high-potential individuals, the greater the improvement in individual and organizational performance. Effective talent management not only drives productivity but also builds a sense of appreciation and engagement among employees, thereby strengthening their commitment to contributing optimally to the organization. Furthermore, high employee competence enhances organizational commitment, as employees with strong abilities and self-confidence tend to demonstrate greater loyalty and responsibility towards their work. This study also found that performance has a positive effect on organizational commitment; high-performing employees tend to feel more satisfied and proud of their work, thus increasing their commitment to the organization.